Visual perception of male body attractiveness - Fan, J. (The Royal Society, 2005)
Based on 69 scanned Chinese male subjects and 25 Caucasian male subjects, the present study showed that the volume height index (VHI) is the most important visual cue to male body attractiveness of young Chinese viewers among the many body parameters examined in the study. VHI alone can explain ca. 73% of the variance of male body attractiveness ratings. The effect of VHI can be fitted with two half bell-shaped exponential curves with an optimal VHI at 17.6 lm(−2) and 18.0 lm(−2) for female raters and male raters, respectively. In addition to VHI, other body parameters or ratios can have small, but significant effects on male body attractiveness. Body proportions associated with fitness will enhance male body attractiveness. It was also found that there is an optimal waist-to-hip ratio (WHR) at 0.8 and deviations from this optimal WHR reduce male body attractiveness.